Correlation between degree of bone invasion and prognosis in carcinoma of the mandibular gingiva: Soft tissue classification based on UICC classification. Issue 5 (September 2015) - Matsushita, Yuki; Yanamoto, Souichi; Yamada, Shin-ichi; Mori, Hitomi; Adachi, Masaki; Takahashi, Hidenori; Naruse, Tomofumi; Ikeda, Hisazumi; Shiraishi, Takeshi; Minamikawa, Tsutomu; Shibuya, Yasuyuki; Komori, Takahide; et al.
Abstract: Objective: The criteria for T4 staging of carcinoma of the mandibular gingiva are controversial. Oral cancer staged as T4 implies "invasion to an adjacent organ" such as the skin, extrinsic muscles of the tongue, masticator space, or mandibular bone. In this study, we compared different T classifications and retrospectively investigated the correlation between each classification and the prognosis of patients with carcinoma of the mandibular gingiva. Methods: We investigated 81 patients with squamous cell carcinoma of the mandibular gingiva treated at two institutions. Results: There was a significant correlation between soft tissue classification and local recurrence ( P < 0.05) and that the correlation with prognosis is borderline significant ( P = 0.05). Conclusions: Soft tissue classification, which does not consider bone invasion, was the most useful for diagnosis, selecting the appropriate surgical procedure, and assessing the correlation to prognosis. We recommended using this classification to define T4. Because this classification is not new but is based on International Union Against Cancer classification, it could be easily adopted. However, the current study is a retrospective analysis of a small number of patients. A multi-institutional, prospective study is necessary to determine the appropriate criteria for the TNM staging of carcinoma of the mandibular gingiva.